A New Pioneering Advancement: Waterlase (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Waterlase™ is a trailblazing tool for dentists which is an amalgamation of laser energy and water. Thisprocess is known as Hydro Photonics. This tool is proficient to perform many conventional dental procedureswith less need for anesthesia. Hard and soft tissue can be cut using Waterlase without applying heat, vibrationor pressure. The dental operator may easily carry out the procedure in the absence of anesthesia. Waterlaselaser decreases post-operative bleeding, pain and swelling and the need for pain medication in many cases.It has been used for a variety of therapies such as hard and soft tissue procedures including caries removal,cavity preparation, endodontic therapy, designing and correcting smile, frenectomy, gingival excision,gingivoplasty, curettage, vestibular deepening, operculum excision, crown lengthening, flap surgery, andosseous surgical procedures,etc.